The branching architecture of artemisia ordosica and its resistance to wind erosion - Qu, Zhiqiang; Li, Zhiguo; Hu, Linxi; Liu, Lianyou; Hu, Xia; Zhang, Guoming; Lv, Yanli; Guo, Lanlan; Yang, Yanyan; Yang, Ziqiong; Han, Guodong (Frontiers in Environmental Science, 2022)
Different branching architectures reflect the adaptation strategies of different plants and affect their resistance to wind erosion. This study presents field-based observations that demonstrate the relationship between the branching architecture of Artemisia ordosica and its resistance to wind erosion. This species is the dominant plant species in the semi-fixed and fixed dunes of the Mu Us Sandy land. The overall bifurcation ratio (OBR) of semi-fixed sandy land is higher than the fixed sandy land 0.27; Similarly, the total stepwise bifurcation ratio (SBR) is higher than the fixed sandy land about 0.74; The length of first levels of total branches is also higher than 8.07. The aerodynamic roughness was greater than the A. ordosica community in the fixed and semi-fixed sandy land than in the bare sandy land. The airflow fields in the cross-wind direction were strongly affected by the windward shape of the plants, which became gradually narrower from the base to the top, while in the leeward direction, the wind speed at different heights behind the plant returned to the incoming airflow velocity. The result confirms that the influence of the windward shape of the plant on the surrounding airflow field is much larger than the influence of plant thickness, porosity or other factors.